Pelatihan Pengelolaan dan Pemusnahan Limbah Obat Rusak dan Kadaluarsa di Desa Kotapulu Kabupaten Sigi - Tandah, Muhamad Rinaldhi; Diana, Khusnul; Adisaputra, Arya Dibyo; Hardani, Ririen (Jurusan Farmasi FMIPA Universitas Tadulako, 2024)
The widespread circulation of illegal drugs poses a serious threat to society as it can have negative impacts on health. In 2019, BPOM Palu confiscated illegal drugs and cosmetics from various areas in Central Sulawesi. A law enforcement operation in Sigi Regency on September 23, 2020, together with the Central Sulawesi Regional Police, successfully seized Class G prescription drugs, traditional medicines, and illegal cosmetics (BPOM Palu, 2022). The main cause of illegal drug circulation is the improper reuse of household drug waste, exploited by irresponsible parties. The use of illegal drugs, which may consist of counterfeit, damaged, or expired items, can endanger health and even lives. One crucial step to prevent this is by managing drug waste properly. Since 2019, BPOM has been conducting awareness campaigns such as